The answer is <span>x - 1 = 3x + 9
All steps are:
</span>Step 1: 4ˣ⁻¹ = 64ˣ⁺³<span>
Step 2: 4</span>ˣ⁻¹ = (4³)ˣ⁺³ <span>
Step 3: 4</span>ˣ⁻¹ = 4³ˣ⁺⁹
Step 4: x - 1 = 3x + 9
Step 5: x - 3x = 1 + 9
Step 6: -2x = 10
Step 7: x = 10/-2
Step 8: x = -5
Answer: The last
Step-by-step explanation: 2 of the x values are the same
Considering there is not much information my best guess would be 175-28x
Answer:
10
Step-by-step explanation:
(2/3) x (15)
is the same as
(2/3) x (15/1)
which means after you multiply them you get:
30/3
which simplifies to:
10